Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Tuấn Đạt
Xem chi tiết
Vũ Lang
Xem chi tiết
Quyên Phạm
Xem chi tiết
Xyz OLM
30 tháng 12 2021 lúc 0:01

Vì a + b + c = 0

<=> (a + b + c)2 = 0

<=> a2 + b2 + c2 = -2(ab + bc + ca)

Khi đó \(\frac{9\left(a^2+b^2+c^2\right)}{\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2}=\frac{-18\left(ab+bc+ca\right)}{2\left(a^2+b^2+c^2-ab-bc-ca\right)}\)

\(=\frac{-18\left(ab+bc+ca\right)}{-6\left(ab+bc+ca\right)}=3\)

Khách vãng lai đã xóa
Xyz OLM
30 tháng 12 2021 lúc 0:05

a2 - 6b2 = ab

<=> (a + 2b)(a - 3b) = 0

<=> \(\orbr{\begin{cases}a=-2b\left(\text{loại}\right)\\a=3b\left(tm\right)\end{cases}}\)

Khi đó \(A=\frac{2ab}{a^2-7b^2}=\frac{6b^2}{2b^2}=3\)

Khách vãng lai đã xóa
Nguyễn Vũ Đức
Xem chi tiết
Hồng Minh Nguyễn Thị
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
14 tháng 12 2017 lúc 8:19

Dai Thang Dinh
Xem chi tiết
 Mashiro Shiina
20 tháng 3 2019 lúc 18:27

\(pt\Leftrightarrow\left(a+b\right)^2+\left(b-2\right)^2=0\)

\(\Leftrightarrow a=-2;b=2\)

Giải tiếp nhé

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
10 tháng 7 2018 lúc 8:52

Chọn D

Đức Anh Gamer
Xem chi tiết